WHAT KIND OF HEALING DOES PSYCHEDELIC-ASSISTED PSYCHOTHERAPY FOSTER? - Shelby, Candice L (PEOPLE: International Journal of Social Sciences, 2019)
World-wide, researchers and practitioners in psychiatry are increasingly interested in the effectiveness of such substances as MDMA, LSA, and psylocibin in treating such disorders as addiction, post-traumatic stress disorder, and other types of depressive and anxiety. Although most of these substances were declared illegal in most countries during the 1970s, research into their use was widespread during the mid-20th century, and has recently returned to the spotlight. Psychotherapy enhanced by some of these substances has been demonstrated to be highly effective where pharmaceuticals have not. People undergoing these therapies appear to be truly healed, rather than merely treated. This, though, raises the philosophical question of what the nature is of the healing that therapy utilizing these substances fosters. Unlike pharmaceutical treatments, these treatments are not based on a biological model, chronically altering brain chemistry; and unlike traditional talk therapies, psychedelic-assisted psychotherapy does not require extended periods of time, or any of the elements associated with Freudian, cognitive behavior, or other psychological models. Using traditional philosophical methods, this paper argues that objections to the use of psychedelics in psychotherapy are unwarranted, and that, in fact, the kind of healing that they bring about is just what our competitive, isolating, and alienating contemporary world needs.